Phase equilibria of the Zn-Ti system: Experiments, first-principles calculations and Calphad assessment. (March 2019) - Liang, Song-Mao; Singh, Harish K.; Zhang, Hongbin; Schmid-Fetzer, Rainer
Abstract: The phase equilibria and thermodynamic properties of the Zn-Ti system have been investigated by experiments, first-principles calculations and Calphad assessment. Differential scanning calorimetry measurement and microstructure characterization confirmed the Zn richest eutectic reaction to occur at 691.3 ± 0.4 K with about 0.27 at% Ti in the liquid. Density functional theory (DFT) calculations have been performed to calculate the finite-temperature heat capacity ( C p ) of the intermetallics, providing also the absolute entropies. A full thermodynamic assessment of the Zn-Ti system has been performed by using the experimental and DFT results obtained in this work together with the collection of all available data from previous publications. In the present work, the Calphad results show good agreement not only in thermodynamic properties with DFT data, but also phase equilibria data with experimental results, especially in the Zn-rich side, which significantly improved from previous Calphad assessment. Phase diagrams including the gas phase have also been calculated and discussed. Highlights: Full thermodynamic assessment of Zn-Ti system for the first time. Key experiments confirm the eutectic temperature and composition at Zn-rich corner. Applied first principles calculations for thermodynamic properties of intermetallics.